ANALYSIS OF CORROSION IN PRODUCTION TUBING USING OLGA SIMULATOR - Astra Agus Pramana; Yusuf Revy Fadillah (PETRO:Jurnal Ilmiah Teknik Perminyakan, 2022)
Corrosion is a problem that occurs in the production system of industrial oil and gas. Control corrosion in tubing production is necessary for maintaining production and well direct as tubing production is the first contact with corrosion fluid and material agent. Corrosion is caused by a chemical reaction between a material and corrosion fluid. A corrosion rate prediction model can be used to predict its rate such as NORSOK and de Waard models. Both methods are used in Olga Simulator software by Schlumberger company that will be used in this paper. Some of the parameters and scenarios that influence corrosion are tested. Evaluation of reservoir pressure 40 bar, 45 bar, 50 bar, temperature 100℃, 125℃, 150℃, mono-ethylene glycol 0%, 20%, and 80% with 66,7%IE and 79,7%IE were used as corrosion inhibitors for looking at the best scenario.